1986
DOI: 10.1111/j.1439-0442.1986.tb00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Effects of Topically Applied Trichothecenes I. Comparative Study of Various Trichothecenes in Mice

Abstract: T-2 toxin, HT-2 toxin, Diacetoxyscirpenol (DAS), Roridin A, Verrucarin A and 3-Acetyldeoxynivalenol(3-AcDON) were dissolved in dimethyl sulfoxide and applied topically to mice. For a mortality study, groups of 10-20 male mice received either 5, 10, 20, 30 or 40mg toxin/kg BW.Further, mixtures of trichothecenes were applied, e. g.: T-2 toxin + DAS + 3-AcDON; T-2 toxin + DAS; T-2 toxin + 3-AcDON; DAS + 3-AcDON. Animals were observed until death or until day 14 after application, and the mortality rates were esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

1986
1986
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…It was also suggested that studies of interactions between trichothecenes be performed (Larsen et al 2004), which, in my opinion, would have little value. It is known that there are interactions between trichothecenes in model systems (Koshinshy and Khachatourians 1992) and in animals (Schiefer et al 1986;Bhavanishankar et al 1988), but their dimension is modest (<5Â) compared to the safety factors in the PMTI for DON.…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that studies of interactions between trichothecenes be performed (Larsen et al 2004), which, in my opinion, would have little value. It is known that there are interactions between trichothecenes in model systems (Koshinshy and Khachatourians 1992) and in animals (Schiefer et al 1986;Bhavanishankar et al 1988), but their dimension is modest (<5Â) compared to the safety factors in the PMTI for DON.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on Stachybotrys chartarum or its specific mycotoxins used ingestion, injection, or dermal application of purified toxins (23)(24)(25)(26)(27)(28)(29). Mouse exposures to S. chartarum spores given intranasally were examined for histologic changes in lung tissue (30,31).…”
mentioning
confidence: 99%
“…At the time of necropsy, gross changes were recorded and thymus, spleen, duodenum and skin were collected and fixed in 10 % formalin. Haematoxylin and eosin stained tissue sections were evaluated without knowledge of the treatment group, and quantitative descriptors were employed (for details, see SCHIEFER and HANCOCK, 1984).…”
Section: Detailsmentioning
confidence: 99%